Self-leadership and Work Role Innovation: Testing a Mediation Model with Goal Orientation and Work Motivation - Curral, Luis (2014)
This article explores the relationship between self-leadership, goal orientation, intrinsic motivation, and innovative behavior. Because innovation requires self-navigation competences we propose that self-leadership skills mediate the relationship between goal orientation and role innovation, as well as between intrinsic motivation and role innovation. To investigate this, 108 employees from three companies, working on the development and implementation of technological solutions, were surveyed on their goal orientation believes, their level of intrinsic motivation, their self-leadership strategies, and the frequency they introduce new procedures on their jobs. Structural equation modelling showed a positive relationship with role innovation for learning goal orientation and intrinsic motivation, but not for performance goal orientation. Self-leadership skills fully mediated the relationship between learning goal orientation and role innovation and partially mediated the relationship between intrinsic motivation and role innovation. Thus, enhancing employees’ self-navigation competences might be an avenue for enhancing their innovative behavior.